Non-destructive evaluation of titanium alloys - Yap, Jin Tong (Nanyang Technological University, 2023)
Non-destructive testing (NDT) plays a critical role in the inspection of the structural integrity of industrial materials such as that of an aircraft wing or fan blades. Among all the NDT techniques, ultrasonic testing has demonstrated high efficiency and reliability, and is widely utilized by many operators around the world. In today’s aerospace industry, titanium alloys are commonly used in aerospace applications and with the use of ultrasonic testing, it can detect and characterize material defects in the titanium alloys. It will then determine whether the material is to be rejected according to official standards. The decision of rejecting or accepting the material will ensure the reliability and safety of the aerospace components.